Effects of assisted reproductive technologies on transposon regulation in the mouse pre-implanted embryo - Carmignac, Virginie; Barberet, Julie; Iranzo, Julian; Quéré, Ronan; Guilleman, Magali; Bourc'his, Déborah; Fauque, Patricia (Human reproduction (Oxford), 2019)
Abstract STUDY QUESTION Do assisted reproductive technologies (ARTs) impact on the expression of transposable elements (TEs) in preimplantation embryos? SUMMARY ANSWER The expression of all TE families is globally increased with mouse embryo culture with differences according to culture medium composition. WHAT IS KNOWN ALREADY Mammalian genomes are subject to global epigenetic reprogramming during early embryogenesis. Whether ARTs could have consequences on this period of acute epigenetic sensitivity is the matter of intense research. So far, most studies have examined the impact of ARTs on the regulation of imprinted genes. However, very little attention has been given to the control of TEs, which exceed by far the number of genes and account for half of the mammalian genomic mass. This is of particular interest as TEs have the ability to modulate gene structure and expression, and show unique regulatory dynamics during the preimplantation period. STUDY DESIGN, SIZE, DURATION Here, we evaluated for the first time the impact of ART procedures (superovulation, in-vitro fertilisation and embryo culture) on the control of different TE types throughout preimplantation development of mouse embryos. We also made use of a mouse model carrying a LINE-1 retrotransposition-reporter transgene to follow parental patterns of transmission and mobilisation. PARTICIPANTS/MATERIALS, SETTING, METHODS Hybrid B6CBA/F1 mice were used for the expression analyses. Relative TE expression was evaluated by using the nCounter quantification methodology (Nanostring®). This quantitative method allowed us to simultaneously follow 15 TE targets. Another technique of quantification (RTqPCR) was also used. A mouse model carrying a LINE-1 retrotransposition-reporter transgene (LINE-1 GF21) was used to follow parental patterns of transmission and mobilisation. MAIN RESULTS AND THE ROLE OF CHANCE We found that the superovulation step did not modify the dynamics nor the level of TE transcription across the preimplantation period. However, upon in-vitro culture, TE expression was globally increased at the blastocyst stage in comparison with in-vivo development. Finally, by monitoring the transmission and mobilisation of a transgenic LINE-1 transposon, we found that in-vitro fertilisation may alter the mendelian rate of paternal inheritance. LARGE SCALE DATA N/A LIMITATIONS, REASONS FOR CAUTION Even though the Nanostring results concerning the dynamics of transcription throughout preimplantation development were based on pools of embryos originating from several females, only two pools were analysed per developmental stage. However, at the blastocyst stage, consistent expressional results were found between the Nanostring technology and the other technique of quantification used, RTqPCR. WIDER IMPLICATIONS OF THE FINDINGS Our findings highlight the sensitivity of TEs to the ART environment and their great potential as biomarkers of culture medium-based effects. STUDY FUNDING/COMPETING INTEREST(S) This work was supported by funding from the 'Agence de la Biomedecine', 'Conseil Régional de Bourgogne' and 'RCT grant from INSERM-DGOS'. The authors have no conflicts of interest to declare.